Results of late gadolinium enhancement in children affected by dilated cardiomyopathy - Muscogiuri, Giuseppe; Ciliberti, Paolo; Mastrodicasa, Domenico; Chinali, Marcello; Rinelli, Gabriele; Santangelo, Teresa P.; Napolitano, Carmela; Leonardi, Benedetta; Secinaro, Aurelio (Frontiers in Pediatrics, 2017)
Background: Little is known about the clinical value of late gadolinium enhancement (LGE), in children affected by dilated cardiomyopathy (DCM). Materials and Methods: We retrospectively evaluated 15 patients (8±6y, 6males) with diagnosis of DCM underwent to cardiac magnetic resonance since 2014. All scans were performed with a 1.5T system (Aera, Siemens). Study protocol included cine steady state free precession sequences, followed by administration of 0.2mmol/kg of gadolinium based contrast agent. Inversion recovery Turbo-Flash sequences, in the same position of cine images, were acquired 10-15 minutes after the injection of contrast agent, in order to assess the presence of late gadolinium enhancement (LGE). The latter was considered positive with a signal intensity >6 SD from normal myocardial tissue. Indexed end-diastolic volume (EDVi) and end-systolic volume (ESVi), and left ventricle (LV) ejection fraction (EF) were calculated by using dedicated software on off-line workstation. Global longitudinal strain and diastolic function was evaluated by echocardiography. Clinical follow up, including death, transplant and listing for heart transplant (MACE) were evaluated. Patients were divided in two different subgroups: negative (Group A) and positive (Group B) for presence of LGE. Statistical analysis was performed by using Mann-Whitney U test (p < 0.05 considered as statistically significant). Results: Seven patients (47%) showed LGE. A global diffuse subendocardial pattern was evident in all patients presenting LGE (7/7, 100%). The following main LV indexes were observed in the two subgroups. Group A: EDVi = 96±33ml, ESVi = 56±29ml, LV EF = 45±10%, global longitudinal strain= -16±5%, E/e’ ratio= 10±3, MACE=1. Group B: EDVi = 130±60ml, ESVi = 89±43ml, LV EF = 31±6%, global longitudinal strain= -13±4%, E/e’ ratio= 9±3, MACE=3. There was no statistically significant difference between the two groups, in terms of EDVi (p: 0.2), ESVi (p: 0.2) and E/e’ ratio (0.9), whereas a significant difference of LV EF, presence of significative mitral regurgitation and global longitudinal strain was observed (respectively: p: 0.03, p: 0.009, p: 0.03). Conclusion: In our population of children with DCM, LGE shows a global diffuse subendocardial pattern. Presence of LGE seems to play a role in these patients determining a worst global systolic function.